2008
DOI: 10.1196/annals.1447.011
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis of β Cells of the Pancreas by Advanced Glycation End‐Products, Important Mediators of Chronic Complications of Diabetes Mellitus

Abstract: We herein report cytotoxicity of advanced glycation end-products (AGEs) on pancreatic beta cells. AGEs stimulated reactive oxygen species (ROS) generation but did not arrest proliferation of the INS-1 cell line. Pancreatic beta cell lines or primary cultured islets possess a receptor for AGE (RAGE), and its expression increased after AGE treatment. TUNEL staining and FACS analysis using annexin V/PI antibodies showed that apoptosis increased in INS-1 cells or primary cultured islets when incubated with BSA con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 10 publications
3
53
2
1
Order By: Relevance
“…52 In both of these studies, high levels of AGEs were shown to result in hyperglycemia. Given that prooxidants such as AGEs are toxic to pancreatic islets [53][54][55] and that anti-AGE agents and diets protect against islet and ␤-cell injury and dysfunction, 30,53 it is possible that AGER1 overexpression could protect against ␤-cell injury as a matter of course. Further studies are required to elucidate the mechanisms involved in these effects.…”
Section: Discussionmentioning
confidence: 99%
“…52 In both of these studies, high levels of AGEs were shown to result in hyperglycemia. Given that prooxidants such as AGEs are toxic to pancreatic islets [53][54][55] and that anti-AGE agents and diets protect against islet and ␤-cell injury and dysfunction, 30,53 it is possible that AGER1 overexpression could protect against ␤-cell injury as a matter of course. Further studies are required to elucidate the mechanisms involved in these effects.…”
Section: Discussionmentioning
confidence: 99%
“…102 Binding to the receptors for AGE (RAGE) on β-cells leads to increased ROS and induction of apoptosis. 103 Reactive oxygen species enhance AGE-induced signaling, which activates pathways associated with inflammation. 104,105 Thus, chronic exposure to elevated concentrations of nutrients, impairment in antioxidant status and activation of the inflammatory response are all inter-related and may contribute to cellular dysfunction and apoptosis (Fig.…”
Section: The Roles Of Oxidative Stress and Inflammation In Epigeneticmentioning
confidence: 99%
“…In the present study, B. crassifolia lowered the level of blood glucose significantly as compared with that of the diabetic control group. Therefore, our data demonstrated that NS protected RIN-5F cells from AGEs-induced oxidative stress which is followed by decreasing insulin gene expression and secretion [Lim et al, 2008]. Although, the serum insulin level of the NS group tended to increase as compared with that of the diabetic control suggesting that NS might partially rescue exhausted pancreatic β-cells of rats from further AGEs-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 59%